Decoding the influence of field surface, tactical positioning, and field zone on tactical networks in youth football - Brito, Â; Freitas, L. (Journal of Human Sport & Exercise, 2025)
This study investigates the impact of different field surfaces on passing networks and tactical performance of youth football teams. Using observational analysis, tactical positioning data were collected, and passing networks were constructed. The results suggest differences in network metrics based on the surface type: average shortest path length F(2.052)=6.099; p<0.006, n2=0.289; betweenness centrality F(2.001)=7.294; P<0.003, n2=0.327; closeness centrality F(2.025)=5.207; p<0.011, n2=0.258; clustering coefficient F(2.032)=23.679; p<0.001, n2=0.612; and radially F(2.001)=6.099; p<0.006, n2=0.289. Closeness centrality varied significantly between tactical positions F(10.009)=1.918, p<0.05, n2=0.466. Passing relationships based on field zones also showed significant differences: average shortest path length F(23.193)=6.057; P<0.001, n2=0.744; betweenness centrality F(23.002)=5.103; p<0.001, n2=0.710; closeness centrality F(23.015)=6.835; p<0.001, n2=0.766; degree F(23.592)=5.298; p<0.001, n2=0.717; radiality F(23.001)=8.366; p<0.001, n2=0.800; and stress F(23.773)=5.302; p<0.001, n2=0.718. This study provides valuable insights for coaches and analysts on optimizing youth soccer performance, highlighting the importance of considering field surface in tactical planning and training strategies.